Identification of phytochemicals in Cleome rutidosperma DC. methanol extract and evaluate its efficacy on some common rice field weeds - Motmainna, Mst.; Juraimi, Abdul Shukor; Hasan, Mahmudul; Binti Asib, Norhayu; Mominul, A. K. M.; Ahmad-Hamdani, Muhammad Saiful (Universiti Putra Malaysia, 2024)
Screening different plant species for herbicidal activity and identifying new allelochemicals with novel structures and phytochemical activity could be promising candidates for reducing the negative consequences of chemical herbicides. Our study aims to investigate the allelopathic substance(s) and herbicidal efficacy of Cleome rutidosperma DC. on rice filed weeds in the lab and glasshouse. The phytochemical constituents of the methanol extract of Cleome rutidosperma were analyzed by high-performance liquid chromatography coupled with electrospray ionization quadrupole time-of-flight mass spectrometry (HPLC-ESI-QTOF-MS). The allelopathic effect of C. rutidosperma has been further studied on the germination and early development of five common rice field weeds: Echinochloa crus-galli (L.) P. Beauv., Fimbristylis miliacea (L.) Vahl, Oryza sativa f. spontanea Roshev., Leptochloa chinensis (L.) Nees, and Cyperus iria L. The seed germination and growth of tested weeds under lab and glasshouse conditions were compared to three concentrations of C. rutidosperma methanol extract at 2.5, 5, and 10% with the control (only distilled water). The results indicated the presence of 64 and 10 known chemicals using positive and negative ionization techniques, the majority of which were toxic. The inhibitory effect of C. rutidosperma was stronger in the lab than in the glasshouse. No seed germination of the tested species was observed when 10% C. rutidosperma extract was applied. The photosynthesis rate of C. iria exhibited a higher reduction (70.56%) compared to other species at higher doses (10%) of C. rutidosperma. These findings demonstrated that C. rutidosperma is a significant source of phytotoxic components and can be used to develop future bio-herbicides. The outcome of this study can be employed in the organic management of weeds and reduce our heavy reliance on synthetic herbicides.